Common fixed points of modified Picard-S iteration process involving two G-nonexpansive mapping in CAT(0) space with directed graph: Sabiya Khatoon, Izhar Uddin, Nuttapol Pakkaranang, Nopparat Wairojjana - Team, Support (Thai Journal of Mathematics, 2020)
The aim of this paper is to bring and study the convergence behaviour of modified Picard-S iteration involving two G-nonexpansive mappings in CAT(0) space with directed graph. We prove Δ and strong convergence theorems for modified Picard-S iteration process in CAT(0) space with a directed graph. We also construct a numerical example to validate our results and to ensure the better rate of convergence of the proposed method with modified Ishikawa iteration, modified S-iteration and Thianwan's new iteration.